Prince Nawruz and His Role in the Political Transformations during the Ilkhanate Rule (681–697 AH) - Assis. Lect. Awad Salman Sajit (Journal of College of Education, 2025)
The Ilkhanate period witnessed the emergence of distinguished figures who played pioneering roles across various fields, thereby contributing significantly to shaping the course of political and military events experienced by the Ilkhanid state. Among these figures was Prince Nawruz ibn Arghun, who assumed a prominent position in influencing the major political transformations that marked this era. Despite the importance and uniqueness of this personality, Prince Nawruz has not received sufficient scholarly attention from specialists in Mongol or Ilkhanid history. This lack of focused academic treatment has resulted in ambiguity surrounding several aspects of his political and historical role. Consequently, this study seeks to shed light on Prince Nawruz and to examine his pivotal role in the political changes that occurred during the Ilkhanate rule between 685–697AH. These political transformations constituted a serious turning point in the history of the Ilkhanid state and nearly led to the collapse of its rule. Through these developments, and owing to his political acumen and strategic skill, Prince Nawruz succeeded in becoming the second most powerful figure in the state. However, his arrogance and vanity prevented him from being satisfied with the authority and prestige he attained. Combined with the envy, hostility, and resentment of his rivals and those affected by his power, this ultimately led them to incite Sultan Ghazan against him. As a result, the Sultan’s attitude toward Nawruz changed, hastening his elimination and eventual execution.